Numerical simulation of axially loaded concrete filled hollow steel section columns at elevated temperatures - Rizalman, Ahmad Nurfaidhi (2016)
Concrete filled hollow steel section columns exhibit various advantages over other materials for similar applications. These include improvement in the structural behaviour with high load bearing capacity for smaller cross-section, better appearance, rapid construction, and high fire resistance without external protection. The study of the thermal-structural behaviour of concrete filled hollow section columns has seen a gradual transition to numerical simulations over an expensive and time consuming physical tests. At present, most of the numerical tools developed in Malaysia for predicting the behaviour of structure in fire is carried out using finite difference method which can be tedious, complicated and very sensitive to numerical errors. Thus, a three-dimensional finite element model, ABAQUS, is proposed to study thermal-structural behaviour of axially loaded concrete filled hollow steel section slender columns for circular and square cross-sections at elevated temperatures. The outer diameter of the circular columns ranged from 141.3 mm to 478 mm and the steel thickness varied from 4.78 mm to 12.79 mm. The outside width of the square columns ranged from 152.4 mm to 350 mm, while the thickness of the steel wall varied from 5.3 mm to 7.7 mm. The proposed numerical models are also ranged based on types of concrete (plain and bar-reinforced concrete), steel yield strength (284 MPa to 350 MPa), concrete compressive strength (18.7 MPa to 58.3 MPa), and thickness of external protection (7 mm to 17 mm). The parameters input used in the model are results of an extensive sensitivity analysis. The accuracy of the proposed numerical model was verified against 21 experimental results and 12 existing models carried out by other researchers as well as with the predictions of the Eurocode 4 simplified calculation model. The verified model was used for a series of parametric studies on the effect of various factors affecting the fire resistance of the columns. The proposed numerical model has proved to produce a better estimation of the fire resistance of the concrete filled hollow steel section columns than the Eurocode 4 simplified model when compared with the fire tests. Based on the analysis and comparison of typical parameters, the effect of sectional shapes, concrete types and thickness of external protection on temperature distribution and structural fire behaviour of the columns are analysed. The result shows that concrete filled hollow section column with circular cross-section has higher fire resistance than square sections